Innate immune responses to three doses of the BNT162b2 mRNA SARS-CoV-2 vaccine - Saresella, Marina; Piancone, Federica; Marventano, Ivana; Hernis, Ambra; Trabattoni, Daria; Invernizzi, Mattia; La Rosa, Francesca; Clerici, Mario (Frontiers in Immunology, 2022)
To explore the effects of SARS-CoV-2-mRNA vaccines on innate immune responses we enrolled 58 individuals who received 3 doses of the BNT162b2 vaccine in a longitudinal study; 45 of these individuals had never been SARS-CoV-2 infected. Results showed that vaccination significantly increased: 1) classical and intermediate inflammatory monocytes, 2) CD56bright, CD56dim, and CD56dim/CD16dim NK cells, and 3) IFNg production as well as perforin and granzyme content by NK cells. Vaccination also reduced expression of the NK inhibitory receptor ILT-2, increasing that of the stimulatory molecule 2DS2. These effects were long-lasting and were boosted by every vaccine dose. Notably, ILT-2 expressing NK cells were reduced even more robustly in COVID-19-recovereed vaccines. BNT162b1 mRNA vaccine is known to induce potent adaptive immune responses; results herein show its ability to modulate innate immune responses as well, offering further support to the indication to proceed with worldwide vaccination efforts to end the SARS-CoV-2 pandemic.